2015
DOI: 10.2217/fon.15.34
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study on Adjuvant Trastuzumab in HER2-Positive Early Breast Cancer Patients

Abstract: Relapse rates are lower in clinical setting compared to clinical trials. Overall, AT is effective in HER2-positive early-stage breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Moreover, the reliance of some studies on published costing data outside their jurisdiction for costing parameters, given its low transferability, may result in unreliable results. Furthermore, it is noted that there may be a difference in the costing data between the actual costs and the costs obtained from published studies since, in reality, approximately 14-17% of HER2-positive EBC patients are not provided with adjuvant trastuzumab [52], specifically for those with advanced age and who have co-morbidities, and about 15% discontinue the adjuvant treatment due to its cardiotoxicity [53]. Nonetheless, the overall input data sources of majority of the studies were of acceptable quality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reliance of some studies on published costing data outside their jurisdiction for costing parameters, given its low transferability, may result in unreliable results. Furthermore, it is noted that there may be a difference in the costing data between the actual costs and the costs obtained from published studies since, in reality, approximately 14-17% of HER2-positive EBC patients are not provided with adjuvant trastuzumab [52], specifically for those with advanced age and who have co-morbidities, and about 15% discontinue the adjuvant treatment due to its cardiotoxicity [53]. Nonetheless, the overall input data sources of majority of the studies were of acceptable quality.…”
Section: Discussionmentioning
confidence: 99%
“…The use rate of trastuzumab in clinical practice was also examined by real-world studies. The real-world evidence from western populations reported a use rate of trastuzumab from 49% to 83%, [15][16][17][18][19] but always with disparities between different races or socioeconomic status. 19,20 In contrast, the use rate of trastuzumab in China was relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study assessing the real-life use of adjuvant trastuzumab in 1245 patients with HER2-positive breast cancer reported a relapse rate of 10.9 % in trastuzumab-treated patients versus 22.6 % in untreated patients (median follow-up 37.4 and 62.1 months, respectively), with lower DFS in relapsed versus non-relapsed patients [ 39 ]. The relapse rate at 5 years was 17 %, which is in line with the BCIRG 006 study and other observational studies, but much lower than that reported in the HERA study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%